1996
DOI: 10.1074/jbc.271.32.19617
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Heat-shock Protein 70 Reaction Cycle by the Mammalian DnaJ Homolog, Hsp40

Abstract: The effects of the human DnaJ homolog, Hsp40, on the ATPase and chaperone functions of the constitutively expressed Hsp70 homolog, Hsc70, were analyzed. Hsp40 stimulates the hydrolysis of ATP by Hsc70, causing a ϳ7-fold increase in its steady-state ATPase activity. In contrast to the prokaryotic Hsp70 system, ATP-hydrolysis and not the release of bound ADP is the rate-limiting step in the overall ATPase cycle of mammalian Hsc70.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
283
2
6

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(315 citation statements)
references
References 49 publications
24
283
2
6
Order By: Relevance
“…Several laboratories have found that the binding of unfolded proteins and peptides to Hsc70 is inhibited by DnaJ homologs (14 -16). On the other hand, studies on the refolding of several proteins by Hsc70 have strongly suggested that DnaJ homologs promote substrate binding to Hsc70 or at the very least are required for refolding to take place (8,17,18). Even in these studies, however, there is controversy as to whether ATP is always required for refolding as well as to whether Hsc70 and DnaJ alone are sufficient for refolding or other factors are also required.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Several laboratories have found that the binding of unfolded proteins and peptides to Hsc70 is inhibited by DnaJ homologs (14 -16). On the other hand, studies on the refolding of several proteins by Hsc70 have strongly suggested that DnaJ homologs promote substrate binding to Hsc70 or at the very least are required for refolding to take place (8,17,18). Even in these studies, however, there is controversy as to whether ATP is always required for refolding as well as to whether Hsc70 and DnaJ alone are sufficient for refolding or other factors are also required.…”
mentioning
confidence: 83%
“…Much of the work on the mechanism of these partner proteins has been carried out with the Escherichia coli Hsc70 protein, DnaK, and its partner proteins, DnaJ and GrpE, which are required for numerous functions of DnaK. Thus far, GrpE homologs have only been found in eukaryotic mitochondria (8), but there are numerous eukaryotic DnaJ homologs that interact with Hsc70 (7,9,10). Some are membrane-bound, such as Sec63 in the endoplasmic reticulum and TiM44 in mitochondria, whereas others are soluble, occurring in the cytoplasm and in the lumens of the endoplasmic reticulum and mitochondria.…”
mentioning
confidence: 99%
“…The observations of Hernandez et al (21) with the PR suggest that YDJ-1 is bound directly to the receptor when it interacts as a co-chaperone with receptorbound hsp70. Inasmuch as hsp40/YDJ-1 promotes the ATPase activity of hsp70 (37) and hsp70 ATPase activity is required for both GR priming by hsp70 and the subsequent activation of the primed receptor complex by hsp90 (5,22), it is reasonable to propose that stimulation of hsp70 ATPase activity is the principal function of hsp40/YDJ-1 in opening of the steroid binding cleft. Although hsp40/YDJ-1 acts on the receptor-bound hsp70, it may also interact directly with the receptor.…”
Section: Fig 12mentioning
confidence: 99%
“…A polypeptide substrate commonly used to study Hsc70 function is firefly luciferase, which has a sensitive and reproducible enzymatic assay. Purified Hsc70 has been shown to assist luciferase refolding in numerous studies (Hohfeld et al, 1995;Minami et al, 1996;Hohfeld and Jentsch, 1997;Terada et al, 1997;Luders et al, 2000;Terada and Mori, 2000). However, in most cases the stress-inducible cochaperone Hsp40 was used, and a direct comparison between all three DJAs with Hsc70 has not yet been reported.…”
Section: Dja Activation Of Hsc70mentioning
confidence: 99%
“…Inhibition of Hsc70 binding should then impair the Tom70 docking step required for import. Alternatively, Hsp40 can activate substrate binding by Hsc70 without strongly interacting with substrate (Minami et al, 1996;Cintron and Toft, 2006). If Hsp40 or some mechanism other than the DJAs was sufficient for Hsc70 binding, the truncated DJAs should have less effect.…”
Section: Dja Interaction With Preproteinmentioning
confidence: 99%